Perspective on Organoboron Chemistry - Kong, Lingbing; Cui, Chunming (Synlett, 2021)
Organoboron compounds play prominent roles in structural, synthetic, and materials chemistry because boron atoms can feature electrophilic, ambiphilic, or nucleophilic character. This perspective briefly describes the most recent progress in organoboron chemistry, focusing on new boron molecules and their applications that have attracted great interest from main-group chemists. The research hotspots arising from these pioneering results are also discussed.1 Introduction2 Diboron Reagents3 Boryl Anions4 Borylenes5 Nucleophilic or Ambiphilic Boron-Containing N-Heterocycles6 Conclusions and Outlook
Keywords: boron; diboron compounds; boryl anions; BN-heterocycles